Acute Pancreatitis and Diabetic Ketoacidosis in Accidental Hypothermia and Hypothermic Myxoedema. Issue 5895 (29th December 1973) - Maclean, D.; Murison, J.; Griffiths, P. D.
Abstract : Serial serum amylase and blood glucose levels were measured in 68 hypothermic (rectal temperature 35°C or less) patients, including 15 who had hypothermic myxoedema (serum protein bound iodine 3·5 μg/100 ml or less). Raised amylase levels were found in 34 patients and probably reflected a mild acute pancreatitis. The high amylase levels correlated with low arterial PO2 levels and significantly with high arterial PCO2 levels and the base deficit but not with the severity or duration of the hypothermia. The acute pancreatitis does not explain why hypothermic patients with myxoedema have a poorer prognosis than those who are euthyroid. The pancreatitis occasionally contributed to the development, sometimes delayed, of diabetic ketoacidosis, blood glucose levels of over 120 mg/100 ml being found in 20 patients. There was a significant correlation between the raised serum amylase levels and the hyperglycaemia. Hypoglycaemia, sometimes profound, was found in 12 patients.